2015
DOI: 10.1007/s00428-015-1784-x
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of TERT promoter and BRAF mutations in cutaneous melanoma is associated with more clinicopathological features of aggressiveness

Abstract: The recently described telomerase reverse transcriptase (TERT) promoter mutations are recurrent in cutaneous melanoma. Several authors have described an association between these molecular alterations, some histological parameters, and patient survival. BRAF mutations are very frequent in melanoma, but their actual role in the evolution of the disease is still unclear. Here, we investigated the relationship of TERT promoter mutations and BRAF mutations with the most relevant clinicopathological parameters, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
66
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 37 publications
8
66
5
Order By: Relevance
“…1 A and B), which result in the de novo creation of an ETS binding motif and are associated with increased transcriptional activity at the TERT promoter (14,15). These observations are consistent with current literature reporting the frequent co-occurrence of BRAF/NRAS and TERT promoter mutations in human melanoma tumors (16,17,24,25).…”
Section: Braf/nras Mutant Melanoma Cell Lines Frequently Display Tertsupporting
confidence: 89%
“…1 A and B), which result in the de novo creation of an ETS binding motif and are associated with increased transcriptional activity at the TERT promoter (14,15). These observations are consistent with current literature reporting the frequent co-occurrence of BRAF/NRAS and TERT promoter mutations in human melanoma tumors (16,17,24,25).…”
Section: Braf/nras Mutant Melanoma Cell Lines Frequently Display Tertsupporting
confidence: 89%
“…Recent studies, in fact, reported a statistical relationship between BRAF and TERT promoter mutations in melanomas [7,24,35]. In particular, in our previous study [21] we found that the coexistence of TERT promoter and BRAF mutations correlated more strongly with most important adverse clinicopathological parameters, including thickness, sentinel node metastases, and absence of regression than either mutation alone. Similar results, notably a significant association between the coexistence of TERT promoter and BRAF mutations and worse outcome in terms of disease-free survival, were reported by Xing et al in papillary thyroid carcinoma [36].…”
Section: Discussionsupporting
confidence: 50%
“…Telomerase activation in cancer has been attributed to several mechanisms, including epigenetic deregulation, as well as genetic amplification of the locus containing the TERT gene [20]. Recently, mutations within the TERT gene promoter, particularly at two positions located at -124 and -146 relative to the ATG start site, were found in melanoma [7,14,21] and in several other human cancers [8][9][10][11][12][13], suggesting a putative role in telomerase activation in malignant cells.…”
Section: Discussionmentioning
confidence: 99%
“…15,16,18,19,22 Functionally, the promoter mutations enhance TERT expression through creation of de novo binding motifs for Ets transcription factors. 15 Many of the Ets transcription factors, including GABP that was specifically shown to bind at sites created by the TERT promoter Out of 300 patients, 17 patients without BRAF/NRAS mutation data and three patients without SNP data were excluded from the analysis.…”
Section: Discussionmentioning
confidence: 99%